Age estimation by pulp/tooth area and width ratios in panoramic images of upper and lower canines among the Iranian population - Bardal, Roghieh; Soltani , Mitra (Brazilian Dental Science, 2021)
Objective: One of the techniques of estimating age in forensic medicine, which is associated with the least trauma in both living individuals and corpses, is to use teeth. Accordingly, the present study aims to determine the relationship between chronological age and pulp-to-tooth area ratio and pulp-to-root width ratio in maxillary and mandibular canines on panoramic radiographs among the Iranian population. Material and Methods: A total of 162 panoramic radiographs were evaluated in the present study. Selected patients were of verified age with the age range of 15-45 years. The pulp-to-tooth area ratio (PTR) and the pulp-to-root width ratio were calculated with AutoCAD 2016 software program in maxillary and mandibular canines at two points of the root. The two points include cemento-enamel Junction (CEJ) and pulp/root width at the quarter of a distance between CEJ and end point of root-canal, which was named WA, WB respectively. The patients’ age was also estimated with the use of linear regression equation. Then each patient’s chronological age and the age estimated using this technique was compared. Results: The relationship between PTR in both canines and WB variable in maxilla with chronological age was inverse and significant (P < 0.05); However, there was no strong correlation coefficient (r Gender had no effect on the results of the study. The mean difference between predicted age and actual age with combined PTR and WB formula was lower than 1 year. When the mean of PTR or WB variables was considered as a predictor, significant results were obtained (P < 0.05), showing a decrease in Standard error of estimation (SEE). The results were not significant when variables of upper PTR and lower PTR and the interaction between them were included in the linear regression model (p > 0.05). Same results were obtained with the variable of WB. Conclusion: Combining the variables of PTR and WB gives better results than using variables alone. Estimation of age with the mean of each variable shows less error than their combination. Keywords Age determination; Canine; Panoramic radiography.